1998
DOI: 10.1172/jci167
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the human histocompatibility leukocyte antigen DR3 transgene reduces the severity of demyelination in a murine model of multiple sclerosis.

Abstract: The role of various MHC genes in determining the progression of multiple sclerosis (MS) remains controversial. The HLA-DR3 gene has been associated with benign relapsing MS in some genetic epidemiologic studies, but with disease progression in others. We induced demyelination in highly susceptible B10.M and B10.Q mice expressing the DR3 (HLA-DRB1*0301) transgene to determine directly the effects of a human transgene by infecting them with Theiler's murine encephalomyelitis virus (TMEV). DR3 ϩ mice experienced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…Transgenic expression of DR3 molecules in mice of a susceptible B10.M (H-2 f ) haplotype developed less demyelination than littermate controls without the DR3 transgene (5). These experiments differed from the present experiments in that the parental mice were immune competent and of a haplotype that develops demyelination.…”
Section: The Humoral Immune Response To Virus Antigens Does Not Explacontrasting
confidence: 86%
See 1 more Smart Citation
“…Transgenic expression of DR3 molecules in mice of a susceptible B10.M (H-2 f ) haplotype developed less demyelination than littermate controls without the DR3 transgene (5). These experiments differed from the present experiments in that the parental mice were immune competent and of a haplotype that develops demyelination.…”
Section: The Humoral Immune Response To Virus Antigens Does Not Explacontrasting
confidence: 86%
“…We then substituted the human class II gene (DR2 or DR3) for the mouse class II response. These mice mount normal class II-restricted CD4 T-cell-mediated immune responses to a number of antigens and infectious agents, (5,14,23,34) and have an intact mouse CD8 ϩ T-cell-restricted endogenous class I major histocompatibility complex (MHC) immune response. Therefore, we could not exclude the contribution of the endogenous mouse MHC class I response to antigen challenge.…”
mentioning
confidence: 99%
“…Intracerebral (i.c.) inoculation of mice with Theiler's murine encephalomyelitis virus (TMEV), is commonly used to study viral demyelination and remyelination of the central nervous system (CNS) (Drescher, Nguyen et al, 1998;Drescher, Zoecklein et al, 2000;Dal Canto & Lipton, 1975;Lipton, 1975;Rodriguez, 1993;Pena Rossi, Delcroix et al, 1997;Rodriguez, Pavelko et al, 1995;Rodriguez, Nabozny et al, 1994;Rodriguez & David, 1985). Because the pathologic changes and subsequent clinical signs of the disease in mice are similar to those observed in humans with multiple sclerosis (MS) TMEV infection of mice is also used to model a hypothetical viral etiology of MS (Dal Canto & Lipton, 1975;Lipton, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study we demonstrated that expression of HLA-DR3 in transgenic mice reduced the severity of TMEV-induced demyelination (Drescher et al, 1998). To understand the role of HLA-DQ polymorphisms in de-myelination and neurologic deficits, in this study we generated mice lacking expression of murine class I and class II molecules that were reconstituted with a single human class II DQ gene and examined the role of HLA-DQ polymorphisms in the TMEV model of MS. We first assessed the contribution of these genes to protection from neuronal disease and then investigated subsequent development of demyelination and progressive neurologic deficits.…”
Section: Introductionmentioning
confidence: 99%